Odpowiedzi

  • Użytkownik Zadane
2010-01-17T19:03:35+01:00
2x+y=3
x+y=1/*(-2)

2x+y=3
-2x-2y=-2
podkreśl
2x i -2x musisz to przedkreslic

-y=-2/:(-1)
y=2
x+y=1
x+2=1
x=1-2
x=-1

x=-1
y=2


2010-01-17T19:04:53+01:00
2x + y =3 I*(-1)
x + y =1 I*2

-2x-y=-3
2x+2y=2
+------------
y=-1

y=-1
x+y=1
y=-1
x-1=1
y=-1
x=1+1

y=-1
x=2
Najlepsza Odpowiedź!
2010-01-17T19:08:19+01:00
2x+y=3
x+y=1→x=1-y

2(1-y)+y=3
2-2y+y=3
-y=3-2
-y=1
y=-1


x=1-y=1-(-1)=1+1=2
była to metoda podstawiania
2x+y=3
x+y=1 /×(-2)

2x+y=3
-2x-2y=-2

y-2y=3-2
-y=1
y=-1

x+y=1
x+(-1)=1
x=1+1
x=2
a to metoda przeciwnych współczynników